(untitled) (Clinics, 2021)
This review aims to investigate the different levels of vitamin D and its role in muscle strength in healthy children and non-athletes. A search conducted in three databases (PubMed, Scopus, and Psycinfo) resulted in 655 articles, which were systematically analyzed and selected based on the following criteria: (a) original cross-sectional studies and clinical trials; (b) healthy children aged 5-11 years; (c) no language restriction or year of publication; and (d) studies that assessed the possible relationship between vitamin D levels and muscle strength. Six studies were included because they met all the inclusion criteria. According to the findings of this review, factors such as sex, skin color, and vitamin D supplementation early in life modulate the levels of vitamin D in the body, and there is a relationship between muscle strength and vitamin D levels. Interestingly, vitamin D supplementation is not always significantly associated with increased muscle grip strength. However, there is a scarcity of studies that aim to analyze the possible effects of different levels of vitamin D on muscle function and neuromuscular variables in physically inactive children and non-athletes without previously diagnosed disease. Further studies are warranted in the future to address the gap in the literature.